The Bruce B. Lawrence Reader : Islam beyond Borders - Lawrence, Bruce B. (Book collections on Project MUSE., 2021)
"Over the course of his career, Bruce B. Lawrence has explored the central elements of Islamicate civilization and Muslim networks. This Reader assembles over two dozen selections of Lawrence's key writings, which range from analyses of premodern and modern Islamic discourses, practices, and institutions to methodological reflections on the contextual study of religion. Six methodologies serve as the organizing rubric: theorizing Islam, revaluing Muslim comparativists, translating Sufism, deconstructing religious modernity, networking Muslims, and reflecting on the Divine. Throughout, Lawrence attributes the resilience of Islam to its cosmopolitan character and Muslims' engagement in cross-cultural dialogue. Several essays also address the central role of institutional Sufism in various phases and domains of Islamic history. The volume concludes with Lawrence's reflections on Islam's spiritual and aesthetic resources in the context of global comity. Modeling what it means to study Islam beyond political and disciplinary borders, as well as a commitment to linking empathetic imagination with critical reflection, this Reader presents Lawrence's prescient contributions to the study of Islam in its broadest arc"--